Germans in South Africa during and in the aftermath of World War Two : the dynamics and contradictions of internment, 1939–1948 - Gess, David Wolfgang; Gess, D. W. (David W.) (Stellenbosch : Stellenbosch University, 2024)

(untitled)
Thesis (DPhil)--Stellenbosch University, 2024.